2018
DOI: 10.1016/j.jplph.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 induces a global metabolic change in basil (Ocimum basilicum L.) and peppermint (Mentha piperita L.) and improves their biological activity

Abstract: Many studies have discussed the influence of elevated carbon dioxide (eCO) on modeling and crop plants. However, much less effort has been dedicated to herbal plants. In this study, a robust monitoring for the levels of 94 primary and secondary metabolites and minerals in two medicinal herbs, basil (Ocimum basilicum L.) and peppermint (Mentha piperita L.), grwon under both ambient (aCO, 360 ppm) and eCO (620 ppm) was performed. We also assessed how the changes in herbal tissue chemistry affected their biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
70
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 58 publications
15
70
2
Order By: Relevance
“…It has been known that the photosynthetic rate, and consequently biomass production, could be improved under the effect of AMF inoculation, as a result of the expected increased nutrients uptake [ 36 ], and also under eCO 2 atmosphere due to the enhancement of the carboxylation reaction of rubisco [ 37 ]. Supporting this hypothesis, the current results revealed that eCO 2 and AMF independently, and to more extent in combination, promoted photosynthetic rate and biomass production in T. vulgare ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been known that the photosynthetic rate, and consequently biomass production, could be improved under the effect of AMF inoculation, as a result of the expected increased nutrients uptake [ 36 ], and also under eCO 2 atmosphere due to the enhancement of the carboxylation reaction of rubisco [ 37 ]. Supporting this hypothesis, the current results revealed that eCO 2 and AMF independently, and to more extent in combination, promoted photosynthetic rate and biomass production in T. vulgare ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, sugars and organic acids are related to taste and flavor [ 47 ], essential amino acids are involved in some biological processes, such as protein synthesis [ 48 ] and a lower saturated/unsaturated fatty acids (SFA/USFA) ratio is linked to cardio-protective effects [ 49 ]. It has been reported that the higher the CO2 levels, the higher the rate of photosynthetic activity, which is linked to the enhancement of the carboxylation reaction of rubisco, the enzyme responsible for CO 2 fixation [ 37 ]. As a consequence of photosynthesis improvement, sugars could be accumulated and also broken down via dark respiration, resulting in production of the precursors necessary for synthesis of different classes of primary and secondary metabolites [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate), oxygen radical absorbance (ORAC) and ferric reducing antioxidant power (FRAP) assays to measure total antioxidant power in Cymbopogon proximus seeds, as described before [32]. Briefly, 0.25 g of the seed powder was extracted in ethanol (80%) and centrifuged at 14,000 rpm for 30 min.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…It was detected by HPLC using a fluorescence detector (excitation, 243 nm; emission, 430 nm). The β-cryptoxanthin contents were extracted in acetone and analyzed by a reversed phase HPLC conducted with a diode array detector [39]. Thiamine was extracted in 0.1 N HCl after incubation of 30 min in a water bath.…”
Section: Metabolite Profiling Of Isolated Treated Legumesmentioning
confidence: 99%